(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This article examines the contribution of cooperatives and micro, small, and medium enterprises (MSMEs) to Indonesia’s economic resilience and sovereignty amid rising geopolitical competition in the Indo-Pacific region. Study Design/Methodology/Approach: The study applies a descriptive qualitative method grounded in Systems Theory and the Resource-Based View. It analyses secondary data drawn from government records, academic sources, and institutional publications using content and thematic analysis. Findings: Cooperatives and MSMEs significantly support national output and community-level economic engagement. However, their role remains peripheral in Indonesia’s geoeconomic orientation. Strengthening their institutional capacity through policy realignment, digital advancement, and deeper integration into regional supply chains is essential to reinforce their resilience and economic sovereignty. Originality/Value: By framing cooperatives and MSMEs within the Astagatra framework, the article highlights their relevance to both social and natural resilience pillars of national strength. Their embeddedness within grassroots economic structures and their adaptive capacity provide a foundation for decentralised economic defence. The article offers a novel perspective by linking community-based economic actors to Indonesia’s long-term national resilience agenda, advancing geostrategic discourse beyond state-centric paradigms.